Missed Physiotherapy Appointment and Its Influence on Cost, Efficiency and Patients’ Outcomes - Fatoye, F.; Olubukola, E. Afolabi; Gebrye, T.; Oyewole, O.O.; Fatoye, C.; Fasuyi, F.; Mbada, C. E. (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. Missed appointments is a significant challenge to efficient running of physiotherapy departments and it has cost implications. In this study, wait time, and pattern, predictors and impact of Missed appointments (MAs) on cost, efficiency and recovery time was assessed among Nigerian patients receiving physiotherapy. Method. In this retrospective study a total of 3,243 physiotherapy appointments were booked between 2009 and 2019 at an Outpatient Physiotherapy Clinic in Nigeria. Data were collected on Missed appointments, on costs of of treatment and on socio-demographic characteristics. The total revenue loss due to missed appointments was calculated as a product of the total of Missed appointments and cost per treatment; recovery time was also estimated.Results. Missed appointments were 1,701 out of 3,243 booked (52.5%) and the average wait time for the first appointment was 9.6 ± 23.2 days. The proportion of  Missed appointments was higher among females (50.2%), patients who were not resident of the same location as the clinic (45.3%), patients with orthopaedic conditions (56.2%) and patients referred from an orthopaedic surgeon (32.8%). Females, those who live within the city, and those with neurological/medical conditions were 1.68, 1.24, and 1.52 times more likely to have Missed appointments compared to males (OR = 1.68, Confidence intervals = 1.44 – 1.96, p = < 0.001), those who live outside the city (OR = 1.24, CI = 1.05 – 1.46, p = 0.01), and to those who have orthopaedic conditions (OR = 1.52, CI = 1.20 – 1.93, p  = < 0.001), respectively. Using per treatment schedule cost of N1000 (an equivalent of $ 2.31), a 52.5% Missed appointments rate resulted in lower efficiency of 76.6% with an efficiency ratio of 0.23. Further, a 52.5% Missed appointments rate could potentially impact patient recovery time by 3402 days if Missed appointments slow a patient recovery process by 2 days.Conclusions. Missed appointments for physiotherapy treatment pose a significant challenge in terms of costs, efficiency, and patient recovery time. Thus, an innovative reminder system may help reduce patients’ non-attendance to physiotherapy and its consequences.